Research results applied to the field of health: how experience impacts the classroom and society (2022)
The Health Sciences Faculty of the Universidad Tecnológica de Pereira has been advancing in the generation of new knowledge and has explored various fields of knowledge. This book presents four pieces of research that have a lot to do with new trends, both in the training of human talent in health, and in the way in which knowledge and technology are applied to solutions to context problems. In this case, it is important to mention the role that high-fidelity clinical simulation has been gaining in the training processes of our students, more specifically the use of theater and the “standardized patients” strategy, in the promotion of professional criteria. The positive impact of a focused training is evident, both in the conceptual development of the individual, and in the appropriation of his role as an agent of social change. The theater promotes an intentional interaction with which knowledge, skills and attitudes can be explored in a medical training process. Likewise, theater has been used as a useful tool in the introduction of therapeutic elements in hospital spaces, such as pediatric, oncology or mental health wards, promoting various ways of interacting with medical staff, or exploring personal aspects. that can improve the clinical evolution of patients. Clinical simulation also contemplates a series of technological elements that, when used for educational purposes, can also promote performance analysis of cognitive, technical, and dexterity skills. This is the case of the clinical simulation put to the service of a CPR skills analysis project, in which, through sensors and performance variables such as force, pressure or response time, they can account for advances in CPR training processes, both for university communities and for health professionals.